Intercultural Communication in Disney Pixar's 'Coco': Unveiling Cultural Traditions and Family Bonds - Akhmad, Mashita Ramadhani; Ariyanti, Lisetyo (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This study examines the Disney movie, Coco (2017) through Stuart Hall’s Cultural Studies Theory and Murray Bowen’s Family System Theory to explore cultural traditions and family dynamics in the movie. Employing a qualitative method and collecting data primarily from documentation, this study investigates how Disney represents Mexican traditional culture, particularly Dia de Los Muertos, the the day of the dead, in maintaining individual identity and protecting family bonds. Hall’s theory emphasizes how the movie portrays cultural traditions and representations. Bowen’s theory reveals the importance of family roles, family reconciliation, emotional dynamics, differentiation of self, and multigenerational transmission. The findings of this study contribute to a deeper understanding of cultural diversity and the complexities of familial dynamics. This study contributes on intercultural communication by illustrating animated movies may be effective and powerful instruments for emotional and cultural education connection.